2018
DOI: 10.1016/j.avsg.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Wall Tension Initiates Interleukin-6 Expression and Abdominal Aortic Dilation

Abstract: Background Hypertension (HTN) has long been associated with abdominal aortic aneurysm (AAA) development, and these cardiovascular pathologies are biochemically characterized by elevated plasma levels of angiotensin II (AngII) as well as interleukin-6 (IL-6). A biologic relationship between HTN and AAA has not been established, however. Accordingly, the objective of this study was to evaluate whether elevated tension may initiate IL-6 production to accumulate monocyte/macrophages and promote dilation of the abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…Quantitative RT-PCR revealed that netrin-1 mRNA ( Ntn1 ) expression was significantly increased in AAA aortas compared to healthy tissues exposed to PBS. A similar expression pattern of inflammatory markers adhesion G-protein-coupled receptor E1 ( Adgre1 ), interleukin 6 ( Il6 ) and the C-C motif chemokine 2 ( Ccl2 ) was observed in the aortas, consistent with previous reports 25 (Fig. 1a ).…”
Section: Resultssupporting
confidence: 91%
“…Quantitative RT-PCR revealed that netrin-1 mRNA ( Ntn1 ) expression was significantly increased in AAA aortas compared to healthy tissues exposed to PBS. A similar expression pattern of inflammatory markers adhesion G-protein-coupled receptor E1 ( Adgre1 ), interleukin 6 ( Il6 ) and the C-C motif chemokine 2 ( Ccl2 ) was observed in the aortas, consistent with previous reports 25 (Fig. 1a ).…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, SMCs are resident cells in aortic tissue that are constantly exposed to hemodynamic and humoral stress that may weakly activate the Jak/STAT3 pathway. To support this notion, it has been demonstrated that cyclic stretch of SMCs induced expression of IL-6 [18]. Such a basal activation of STAT3 would be augmented in smSocs3-KO, resulting in the chronic activation of STAT3 as observed in our study.…”
Section: Difference In Cell Types and Time Course Of Stat3 Activationsupporting
confidence: 85%
“…The Ingenuity Pathway Analysis (IPA) estimates increased activities of myometrial expansion/remodeling associated TGFβ, PDGF, ERK, and STAT, inflammation management linked TNF and AP‐1, as well as myometrial contraction related p53 signaling, among others (Tables and S4). Changes of these molecular activities appear to be evolutionarily conserved, as evidenced by a similar observation that compares transcriptomic profiles of the mouse myometrium between 18.5 days post coitus and virgin (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE17021, Tables and S5). Notably, majority of the subset of DEGs that match IPA curated glucose downstream targets exhibits changes of gene expression consistent with the response to glucose treatment (Tables , S4 and S5), which suggests relatively higher glucose utilization at the TP stage.…”
Section: Resultsmentioning
confidence: 68%